A Drug Holiday Reduces the Frequency and Severity of Medication‐Related Osteonecrosis of the Jaw in a Minipig Model. (10th August 2020) - Otto, Sven; Pautke, Christoph; Arens, Daniel; Poxleitner, Philipp; Eberli, Ursula; Nehrbass, Dirk; Zeiter, Stephan; Stoddart, Martin J
ABSTRACT: Treatment of medication‐related osteonecrosis of the jaw (MRONJ) is challenging and no clear consensus has been achieved. This study investigated preventive measures recommended for tooth extractions under antiresorptive (AR) treatment and the role of discontinuation of AR therapy to avoid the onset of MRONJ in a minipig model. Thirty‐six Göttingen minipigs were divided into four groups. Group 1 (negative control): tooth extractions but no zoledronate (ZOL). Group 2 (positive control): weekly ZOL infusions for 12 weeks followed by tooth extractions without wound management followed by 8 weeks of ZOL treatment. Group 3: weekly ZOL infusions for 12 weeks followed by tooth extractions; surgical wound management (resection of sharp bone edges, mucoperiosteal coverage); and continuation of ZOL infusions for 8 weeks plus antibiotic treatment. Group 4: 12 weeks of ZOL infusions followed by a drug holiday for 6 weeks. Tooth extractions with preventive wound management followed by antibiotic treatment for 8 weeks but no ZOL infusions. Jawbones were subjected to macroscopic, radiological (CT and micro‐CT) and histopathological investigations. No clinical cases of MRONJ were observed in the negative group, in the positive control all animals developed MRONJ. Group 3 developed MRONJ in 83% of cases. With a drug holiday, 40% developed MRONJ in areas of tooth extraction. This is the first large animal model that reduces the occurrence of MRONJ following tooth extraction by the implementation of a drug holiday combined with antibiotic prophylaxis and smoothening of sharp bony edges. © 2020 The Authors. Journal of Bone and Mineral Research published by American Society for Bone and Mineral Research..